Sistemática, morfología y biología del gorgojo de la acelga, Fedlerella Papp, sp., en el Perú - Ferrer, F.; Simon, J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The present work tries to present some general concepts on the "salt wort weevil", Fiedlerella Papp, sp. such as geographical distribution, sistematic, morphology and biology. The lack of knowledge of its habits, and all the phases, in Peruvian and foreign literature, has been a cause of many difficulties. This work, in a considerable way, has enabled us to overcome this difficulty. In order to obtain data about the geographical distribution of the Fiedlerella Papp, sp, survey have been carried out in various horticultural zones of the country to compile data directly from agricultural experts which work in these zones of Perú. Entomologists from other countries were also consulted. The best taxonomists on the family Curculionidae and genus Conotrachelus were consulted regarding the identification of the insect. Morphological studies have been carried out even though there is little foreign literature on the subject. Biological and ecological work has been carried out at the Department of Entomology, La Molina Experiment Station and the Agrarian University, Lima, utilizing bioclimatical cabinet and special plant pots for this purpose.